Perubahan Komposisi Kasein pada Permukaan Globula Minyak sebagai Pengaruh Pengingkatan Konsentrasi Fosfolipida selama Emulsifikasi - Teti Estiasih (agriTECH, 2005)
Casein and phospholipids are natural compounds usually used concomitantly as emulsifier. This research is conducted to elucidate the adsorbed casein composition that stabilized oil globule interface during fish oil emulsification as affected by phospholipids concentration. Each casein has different behaviour at oil globule interface. The results showed the changes of adsorbed a A and fc casein at oil globule interface because of phospholipids addition. Among caseins, a casein has prefrence to desorb, 8 casein has preference to adsorb, and K casein has no preference to adsorb Cr desorb. Their preferences to adsorb or desorb are influenced by their surface activities and layer properties. Casein compositional changes are caused by caseinsphospholipids complex formation. This complex has less preference to adsorb at oil globule interface.